Risk of burnout among early career mental health professionals. Issue 9 (20th February 2014) - Volpe, U.; Luciano, M.; Palumbo, C.; Sampogna, G.; Del Vecchio, V.; Fiorillo, A.
<x xml:space="preserve">Abstract</x> Accessible summary Burnout is a stress‐related syndrome that often affects mental health professionals (MHPs) and may have serious consequences on personal well‐being as well as on the quality of provided psychiatric care. Established literature shows a high risk to develop burnout among MHPs. Few data are available on the incidence and on the clinical implications of the burnout syndrome in the early phases of MHP professional career. We confirmed the presence of burnout among early career MHPs: early career psychiatrists showed a lower sense of personal accomplishment, while non‐medical MHPs tended to have more depersonalization and suffered from higher levels of depression. Specific programmes to identify the presence of the burnout syndrome and to cope with it should be taught within mental health training curricula. Abstract Burnout is a stress‐related syndrome that often affects professionals working in emotionally loaded and highly interpersonal environments. Mental health professionals (MHPs) are long known to be at high risk to develop the burnout syndrome, but this has rarely been investigated in professionals in an early phase of career. The aim of the present study was to evaluate the presence of the burnout syndrome and of depressive symptoms among early career psychiatrists and 'non‐medical' MHPs. One hundred MHPs (including 50 psychiatrists and 50 non‐medical MHPs) were screened for the presence of burnout and depression, with the Maslach Burnout Inventory and the Beck Depression Inventory – revised, respectively. The relationships of burnout with socio‐demographical and professional characteristics were also explored. We confirmed the presence of burnout among both groups of early career MHPs, but psychiatrists had a significantly higher degree of emotional exhaustion and a lower sense of personal accomplishment, while non‐medical MHPs adopted more frequently depersonalization as a coping strategy and had higher scores for depression, which is associated with higher level of burnout. The risk of developing burnout should be properly addressed in training curricula and strategies to overcome it should be systematically taught, in order to promote personal well‐being and efficient team work in mental health settings.